2010
DOI: 10.1084/jem.20100734
|View full text |Cite
|
Sign up to set email alerts
|

CD11c depletion severely disrupts Th2 induction and development in vivo

Abstract: Although dendritic cells (DCs) are adept initiators of CD4+ T cell responses, their fundamental importance in this regard in Th2 settings remains to be demonstrated. We have used CD11c–diphtheria toxin (DTx) receptor mice to deplete CD11c+ cells during the priming stage of the CD4+ Th2 response against the parasitic helminth Schistosoma mansoni. DTx treatment significantly depleted CD11c+ DCs from all tissues tested, with 70–80% efficacy. Even this incomplete depletion resulted in dramatically impaired CD4+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
261
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(281 citation statements)
references
References 30 publications
17
261
3
Order By: Relevance
“…In contrast, we have established that DCs pulsed with SEA are capable inducers of Th2 responses both in vitro and in vivo, despite failing to upregulate traditional markers of activation (5). Although it has been debated recently whether DCs are needed to prime Th2 responses (4), we have definitively shown that Th2 priming to schistosomes is dependent on CD11c + DCs (25).…”
Section: Il-4 Up-regulates DC Expression Of Multiple Markers Of Altermentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, we have established that DCs pulsed with SEA are capable inducers of Th2 responses both in vitro and in vivo, despite failing to upregulate traditional markers of activation (5). Although it has been debated recently whether DCs are needed to prime Th2 responses (4), we have definitively shown that Th2 priming to schistosomes is dependent on CD11c + DCs (25).…”
Section: Il-4 Up-regulates DC Expression Of Multiple Markers Of Altermentioning
confidence: 73%
“…C57BL/6, BALB/c, Retnla −/− , IL-10eGFPxDOG, KN2 (C57BL/6), Il4ra −/− , and OTII mice (20,23,25,29,30) were maintained under specific pathogen-free conditions at the University of Edinburgh. Experiments were conducted under a Project License granted by the Home Office (United Kingdom) in accordance with local guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…CD45.1 + C57BL/6 mice (59) were provided by S. M. Anderton, University of Edinburgh. CD11C-DOG mice (28) were provided by A. S. MacDonald, University of Edinburgh. Mice were bred under specific pathogen-free conditions at the University of Edinburgh.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, some studies suggest that ILC, 129-131 basophils, [132][133][134] and eosinophils 135,136 can express major histocompatibility complex class II and directly prime Th2 responses, notably upon N. brasiliensis 131 and T. muris 132 infections, with each cell type having been shown to migrate to the mesenteric lymph nodes during infection. 85,87,137,138 However, given that protective immunity is abolished in mice where all 139,140 or specific subsets 104-106,108,109 of dendritic cells have been depleted, it is perhaps more likely that these other innate cells contribute to local tissue immunity by promoting dendritic cell activation, or by further enhancing the cytokine response of mature T cells that have migrated to the infected tissue. 53 Moreover, dendritic cells are responsive not only to cytokines produced by other innate cells, but also to epithelium-derived cytokines, including TSLP, 54,[141][142][143] IL-25, 144 and IL-33, 52,145 thus potentially bypassing ILC2 and granulocytes entirely.…”
Section: Inductionmentioning
confidence: 99%